Biology of Cochlochila bullita Stal as potential pest of Orthosiphon aristatus (blume) miq. in Malaysia - Tan, Li Peng (2014)
Cochlochila bullita (Stål) is an importance pest in some Asia countries such as India, Kanpur and Thailand attacking plants form the genus Ocimum, herein its common name, ocimum tingid. Cochlochila bullita is first recorded in Malaysia in the year 2009, attacking one of the important medicinal herbs in this country, the Orthosiphon aristatus (Blume) Miq. Biology of this pest was studied to get a deeper understanding of this bug associated with O. aristatus, which will lead to better integrated management on this pest. Morphology and morphometric of C. bullita were described and measured from 15 samples of all developmental stages of this bug in order to provide the fundamental reference for identification. From here, C. bullita possessed a body length and width ratio for about 1.51 to 1.59 mm and the head capsule width was recommended to distinguish the instars. Life-tables of this pest on O. aristatus and Ocimum basilicum Linnaeus were constructed by analyzing the life-parameters from 10 cohorts on each plant. Results showed that on O. aristatus significantly higher finite rate of increase (λ), 1.07 and intrinsic rate of increase (rm), 0.07 were obtained and thus suggest that C. bullita performed better on O. aristatus. The preferences of C. bullita toward these two plants were also examined, it preferred O. aristatus; with a notable feeding preference and relatively higher oviposition preference. The reason of this phenomenon was presumed related to the trichomes density of the plants; hence a further investigation on the correlation between the trichomes density and the number of eggs deposited was conducted. Strong, positive and significant correlation was found on the O. aristatus. Some behavioural studies were carried out, particularly the mating behaviour and maternal care of this species to comprehend how this bug adapts to produce and ensure the succession of its own kinds. One male was freely mixed around with five females in 7 days. Results showed that the male C. bullita was able to fertilize maximum up to four females within the given periods. In the other hand, females were tested for their maternal care, samples collected from the field were tested by provoking the females with a standard protocol; no aggressive approach were shown by the females and hence concluded that this bug possessed only passive guarding behaviour. Injuries caused by this bug were assessed by measuring the injury area, chlorophyll content and faeces production. Results showed a significant higher injury area, faeces production and chlorophyll depletion on O. aristatus. Water content was presumed play a role in the susceptibility of O. aristatus; as O. basilicum having higher water content 91% than O. aristatus with only 88%. After all, O. aristatus is attractive to C. bullita but the tolerance of this plant towards the infestation of the bug is relatively low. Water content and the trichomes density of the plant were believed that contributed to this selectivity and susceptibility. Knowledge of the biology assists in identifying, recognizing and monitoring the insect pest is a important input towards develop a better management strategy for this pest.